Food and nutrition literacy: an education booklet and video on ultra-processed food. (20th October 2021) - Pereira de Araújo, T; Moraes, M de; Afonso, C; Rodrigues, S
Abstract: Background: The COVID-19 pandemic appears to have contributed to change in eating habits for a significant part of the Portuguese population. The increase in the snacks consumption during the confinement period was reported by almost a third of the population. Often the snacks chosen are ultra-processed foods: industrial formulations that include excess of sugar, oils, fats, salt, and additives, antioxidant, stabilizers and preservatives substances in their ingredients. Excessive ultra-processed food consumption has been associated with worse health indicators. Objectives: To develop informative educational material about ultra-processed foods and their health risks to be available to the general Portuguese population, and thus to promote food and nutrition literacy. Results: The development of this new tool started in September 2020 and in April 2021 the booklet was approved by the UPPER Project team to be made available through digital media (cell phone, computer, laptop and tablet) or print. The booklet contains 33 pages with illustrative images and simple and didactic language. It is focused in seven main topics: "What are ultra-processed foods?", "Which are they?", "How to recognize them when purchasing?", "What are worth for?", "What is the relationship with health?", and "What foods to choose?". A short video with 2 minutes duration, summarizing and explaining the booklet, was also produced. The booklet impact will be piloted in a school intervention project that has been designed and submitted for ethical approval. Conclusions: The developed booklet and explanatory video are didactic materials in simple language to achieve all general Portuguese population. Key messages: The booklet is an instrument intending to improve literacy in ultra-processed foods. The booklet is a tool that can be used in health promotion programs and public policies in food and nutrition.